Manajemen Penerimaan Santri Baru Di Pondok Pesantren Busra Chalid Palangka Raya - Ajatul Ajatul; A. Fadchur Rahman Z. (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine how the management of admission of new students at Busra Chalid Islamic Boarding School in Palangka Raya. The research method used is descriptive method using a qualitative approach. The techniques used in data collection are observation, interview, and documentation. Data were obtained from observations and interviews with the subjects of this study, namely the head of the boarding school, the chairman of the new student admission committee, and several new student admission committee members at Busra Chalid Islamic Boarding School in Palangka Raya. The results of this study indicate that, the management activities of new santri admission include the admission planning process and the implementation of santri admission. The process of implementing new student admission activities at Busra Chalid Islamic Boarding School Palangka Raya includes: 1) Formation of the New Santri Admission Committee. 2) Meeting of the New Student Admission Committee. 3) Making and installing admission announcements. 4) Registration. 5) Selection. 6) Determination of accepted students. 7) Announcement of accepted students. 8) Re-registration and the last process, namely; 9) Student Orientation.